The Relationship Between The Degree Of Arcus Pedis And The Degree Of Vertebral Curve In Children - Naufal, Adnan Faris; Putri , Nuristiqomah Dwi; Setiawan, Arif; Kurnia, Pramudya; Fitri, Anida Azkia (Universitas Muhammadiyah Surakarta, 2025)
Background: Spinal health is the most important part of a child's body posture. Age 2-6 years is a period of rapid growth and during this period the vertebral curve will develop rapidly too. The greater the degree of lateral vertebral curve, the more it will result in a posture abnormality called scoliosis. One of the factors that influences body posture abnormalities is the degree of arcus pedis, which normally forms in the first five years of development in children aged 2-6 years. The degree of the vertebral curve can be measured using a scoliometer and the degree of the arcus pedis using the footprint test (Clarke's Angle). This research aims to see whether there is a relationship between the degree of Arcus pedis and the degree of vertebral curve in children 4-6 years old in the Kartasura area. Methods: This research is quantitative research with research methods using univariate analysis, data normality and bivariate. The number of respondents was 565, and the method used was purposive sampling with inclusion, exclusion and dropout criteria. Results: The results of the correlation test using the Nonparametric Correlation Test with the Spearman Rank Test show that there is no relationship between the degree of the Arcus pedis and the degree of the vertebra with a p-value of 0.228 (p>0.05) and the correlation level is very weak (0.051) and the direction of the relationship is positive or unidirectional. Conclusion: There is no relationship between the degree of arcus pedis and the degree of vertebral curve in children aged 4-6 years in the Kartasura area.